Come buy, come buy : shopping and the culture of consumption in Victorian women's writing - Lysack, Krista (Ohio University Press, 2008)
From the 1860s through the early twentieth century, Great Britain saw the rise of the department store and the institutionalization of a gendered sphere of consumption. Come Buy, Come Buy considers representations of the female shopper in British women's writing and demonstrates how women's shopping practices are materialized as forms of narrative, poetic, and cultural inscription, showing how women writers emphasize consumerism as productive of pleasure rather than the condition of seduction or loss. Krista Lysack examines works by Christina Rossetti, Mary Elizabeth Braddon, George Eliot, and Michael Field, as well as the suffragist newspaper Votes for Women, in order to challenge the dominant construction of Victorian femininity as characterized by self-renunciation and the regulation of appetite. Come Buy, Come Buy considers not only literary works, but also a variety of archival sources (shopping guides, women's fashion magazines, household management guides, newspapers, and advertisements) and cultural practices (department store shopping, shoplifting and kleptomania, domestic economy, and suffragette shopkeeping). This wealth of sources reveals unexpected relationships between consumption, identity, and citizenship, as Lysack traces a genealogy of the woman shopper from dissident domestic spender to aesthetic salonière, from curious shop-gazer to political radical. --From publisher's description.